Effects of dexmedetomidine pretreatment on rats with sepsis-induced acute kidney injury and miR-146a expression - Ni, Jinping; He, Jiang; Kang, Li; Zhong, Zhidong; Wang, Liren; Yin, Shuzhou (Cellular and Molecular Biology, 2020)
The current research aimed to study the effects of dexmedetomidine (DEX) pretreatment on rats with sepsis-induced acute kidney injury (SAKI) and miR-146a expression. The model of SAKI was established through the tail vein injection of lipopolysaccharide (LSP). We used an automatic biochemical analyzer to detect serum urea nitrogen (BUN) and creatinine (Cre) levels. The expression levels of urine KIM-1 and NGAL and serum IL-1Î² and IL-6 were analyzed by enzyme-linked immunosorbent assay (ELISA). The content and activity of superoxide dismutase (SOD) were detected by the xanthine oxidase method. The content of malondialdehyde (MDA) was determined by the thiobarbituric acid (TBA) method. Reactive oxygen species (ROS) was detected by fluorescent probe DCFH-DA. Catalase (CAT) was detected by potassium permanganate titration. The expression level of miR-146a in the renal tissue and serum was detected by RT-PCR. The expression levels of Nrf2 and HO-1 proteins were detected by Western blot. Compared with those in the model group, rats in the DEX group had significantly lower expression levels of serum BUN, Cre, IL-1Î², and IL-6, and oxidant markers MDA and ROS, but significantly higher expression levels of miR-146a and antioxidant markers SOD and CAT. DEX pretreatment could improve the kidney morphology, injury severity, and Nrf2 and HO-1 proteins of rats with SAKI. In conclusion, DEX can improve oxidative stress and inflammatory responses in rats with SAKI, reduce the severity of the renal injury, and up-regulate the expression level of miR-146a.